1981
DOI: 10.1002/jlac.198119811217
|View full text |Cite
|
Sign up to set email alerts
|

Identifizierung, Strukturableitung und Synthese bisher unbekannter Urofuransäuren im menschlichen Blut

Abstract: Menschliches Blut enthait die bisher unbekannte 3-Carboxy-4-methyl-5-(l-oxopropyl)-2-furanpropansaure (4) und die 3-Carboxy-4-methyl-5-(l-hydroxypropyl)-2-furanpropansaure (5). Ihre aus Massenspektren abgeleiteten Strukturen wurden durch Synthese sichergestellt: 3-Oxoadipinsaure-dimethylester (11) wurde mit Hydroxyaceton in Gegenwart von Zinkchlorid zu 3-Methoxycarbonyl-4-methyl-2-furanpropans~ure-methylester (12) kondensiert. Nachfolgende Acylierung von 12 mit Propionsaureanhydrid ergab 3-Methoxycarbonyl-4-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

1982
1982
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 10 publications
1
10
0
1
Order By: Relevance
“…Structually related substances designated as urofuranic acids. 3-carboxy-4-methyl-5-pentyl-2-furanpropanoic acid, 3-carboxy-4-methyl-5-(l-oxopropyl)-2-furanpropanoic acid and 3-carboxy-4-methyl-5-(l-hydroxypropyl)-2-furanpropanoic acid, have also been detected in both urineandserum obtained from healthy subjects [16,17,21,22]. Liebich et al [23] have recently reported the increased concentration of 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid in plasma from patients with chronic renal failure by using gas chromatography-mass spec trometry.…”
Section: Discussionmentioning
confidence: 99%
“…Structually related substances designated as urofuranic acids. 3-carboxy-4-methyl-5-pentyl-2-furanpropanoic acid, 3-carboxy-4-methyl-5-(l-oxopropyl)-2-furanpropanoic acid and 3-carboxy-4-methyl-5-(l-hydroxypropyl)-2-furanpropanoic acid, have also been detected in both urineandserum obtained from healthy subjects [16,17,21,22]. Liebich et al [23] have recently reported the increased concentration of 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid in plasma from patients with chronic renal failure by using gas chromatography-mass spec trometry.…”
Section: Discussionmentioning
confidence: 99%
“…3-Carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) was chemically synthesized. 10) Organic solvents used for CsA determination in biological fluids were of HPLC grade. All other chemicals were of reagent grade and used without further purification.…”
Section: Chemicalsmentioning
confidence: 99%
“…CMPF is a trace constituent of urine and blood of healthy subjects [1,4]. Furanoid fatty acids with similar chemical structures were first found in the livers and testes of several fish species as constituents of lipids [5,6], but the source and metabolism of CMPF remain unknown.…”
Section: Introductionmentioning
confidence: 99%